"Will I come home incontinent?" A retrospective file review: Incidence of development of incontinence and correlation with length of stay in acute settings for people with dementia or cognitive impairment aged 65 years and over. Issue 1 (March 2016) - Furlanetto, Kate; Emond, Katherine
Summary: Aim: The aim of the retrospective file review is to obtain incidence of the development of incontinence at time of discharge from an acute/sub-acute care setting for patients who were aged 65 years and over, diagnosed with dementia or cognitive impairment, ambulant and continent pre-admission. Along with, identifying correlation between length of stay and development of incontinence. The data were obtained to measure a need for recommendations related to continence promotion in hospitals. It is hypothesised that the sample group are at risk of developing incontinence throughout their stay. Method: Files for the sample group who were admitted to a regional Victorian hospital acute/sub-acute care over a two-year period were reviewed. A total of 182 files were reviewed, of which 100 files met the inclusion criteria. Results: The study revealed a significant relationship between admission and the development of incontinence for the sample group ( p = .007). At time of discharge from the hospital, 36% suffered urinary incontinence. Of the 36%, 2% also developed new faecal incontinence at time of discharge. A further 21% of patients also experienced an episode of urinary incontinence throughout their stay, but were continent at discharge. An independent-sample t -test was conducted to compare mean length of stay between the group that remained continent ( M = 15.88, SD = 13.028) and the group that developed incontinence ( M = 24.33, SD = 19.497); t (98) = 2.586, p = .011 (two-tailed). Conclusion: Statistically significant results confirm the hypothesis' that the; sample group are at significant risk of developing incontinence throughout a hospital admission, and increased length of stay increases the likelihood of developing a form of incontinence.